2007
DOI: 10.1128/aem.02986-06
|View full text |Cite
|
Sign up to set email alerts
|

Flux Analysis of Central Metabolic Pathways in Geobacter metallireducens during Reduction of Soluble Fe(III)-Nitrilotriacetic Acid

Abstract: We analyzed the carbon fluxes in the central metabolism of Geobacter metallireducens strain GS-15 using 13 C isotopomer modeling. Acetate labeled in the first or second position was the sole carbon source, and Fenitrilotriacetic acid was the sole terminal electron acceptor. The measured labeled acetate uptake rate was 21 mmol/g (dry weight)/h in the exponential growth phase. The resulting isotope labeling pattern of amino acids allowed an accurate determination of the in vivo global metabolic reaction rates (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…Similar results were observed in E. coli respiring with acetate, with 30% of flux from isocitrate going to the glyoxylate shunt and 70% through the lower TCA cycle (35). A 13 C-labeling study of Geobacter metallireducens showed high TCA cycle flux from acetate while respiring with Fe 3ϩ with zero flux through the glyoxylate shunt (36). However, this depiction was misleading as there is nothing in the genome sequence to suggest that the glyoxylate shunt exists in G. metallireducens and rather pyruvate synthase is likely critical to assimilate acetate.…”
Section: Discussionsupporting
confidence: 65%
“…Similar results were observed in E. coli respiring with acetate, with 30% of flux from isocitrate going to the glyoxylate shunt and 70% through the lower TCA cycle (35). A 13 C-labeling study of Geobacter metallireducens showed high TCA cycle flux from acetate while respiring with Fe 3ϩ with zero flux through the glyoxylate shunt (36). However, this depiction was misleading as there is nothing in the genome sequence to suggest that the glyoxylate shunt exists in G. metallireducens and rather pyruvate synthase is likely critical to assimilate acetate.…”
Section: Discussionsupporting
confidence: 65%
“…2). The fluxes are consistent with those of 13 C tracer experiments observed in the isotopic data of Tang et al (43), which showed that the TCA cycle encompassed ϳ90% of the acetate uptake flux, with an additional ϳ8% of acetate flowing through the TCA cycle being used for amino acid and lipid production, and the remainder of the acetate uptake flux passed through the pentose-phosphate pathway and gluconeogenesis. Along with the FB model, the kinetic model predicted that for lower acetate uptake rates, acetate is channeled preferentially into the TCA cycle, leading to low growth efficiency.…”
Section: Resultssupporting
confidence: 77%
“…Within the data sets, there was good correspondence in general trends between in silico relative fluxes and protein abundances. Previous studies have indicated that up to 90% of carbon flux through Geobacter strains is directed through respiratory pathways rather than toward biosynthesis (57). Consistent with this observation, the highest in silico fluxes and protein abundances were observed for proteins associated with the activation of acetate (via an acetyl coenzyme A [acetylCoA] hydrolase/transferase enzyme) and the incorporation of acetyl-CoA into the tricarboxylic acid (TCA) cycle (via citrate synthase).…”
Section: Resultssupporting
confidence: 69%